Australia : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
Property price inflation has accelerated during the last few years, propelled by low mortgage rates, poor returns from alternative investments, strong employment and immigration, and tax incentives. Strong housing demand has led to a substantial rise in housing prices. Most industrial countries face significant fiscal pressures over the longer term associated with population aging and rising health care costs. Significant uncertainty surrounds projections of future fiscal costs. One comprehensive way to take account of this uncertainty for formulating policy decisions is through stochastic simulation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet